Operational Characterization of Pressure Regulating Valves - M. V. Talamini Junior; A. C. S. de Araujo; A. P. de Camargo; E. Saretta; J. A. Frizzone (The Scientific World Journal)
The functionality of pressure regulating valves (PRVs) is important for proper uniformity and efficiency of irrigation during center pivot irrigation, especially when the center pivot operates on sloping terrain. In practice, the regulated pressure at the PRV outlet is slightly influenced by its inlet pressure, the flow rate through it, and hysteresis effects. The objectives of this work were (a) to evaluate operational characteristics of PRVs based on requirements stated by ISO 10522 (1993) and (b) to model the regulated pressure as a function of inlet pressure and flow rate through the valve considering hysteresis. We carried out tests to evaluate regulation uniformity, regulation curve, hysteresis, and the regulated pressure as function of flow rate and inlet pressure. The following three models of PRVs were evaluated: 10 PSI, 15 PSI, and 20 PSI. For each model, three samples were tested under increasing and decreasing conditions of inlet pressure, within the range from 49.03 to 784.53 kPa, with increments of 49.03 kPa. In addition, flow rates were tested within the range of 0 and 4 m3 h−1. From the gathered data, models to predict outlet pressure as a function of inlet pressure and flow rate were fitted.